Spectrum and subcellular determinants of fluorinated anesthetic-mediated proximal tubular injury. - Lochhead, K. M. (1997)
Currently used fluorinated anesthetics are chemically related to methoxyflurane (MF), a drug that caused many cases of clinical acute renal failure during previous widespread use. To determine whether newer fluorinated anesthetics might also have nephrotoxic effects, three currently used agents (isoflurane (IF), sevoflurane (SF), and desflurane) or MF were added to rat proximal tubular segments, followed by assessments of cell integrity (ATP levels and percent lactic dehydrogenase release). Ether served as a negative control. MF, IF, and SF each induced lethal proximal tubular segment injury (up to 92, 71, and 30% lactic dehydrogenase release, respectively) and massive ATP depletion. ATP losses were observed at or near clinically relevant drug levels, they preceded lethal injury, and they correlated with approximately 50% and approximately 100% reductions in total and Na,K-ATPase-driven respiration, respectively. Clinically relevant inorganic fluoride levels simulated fluorinated anesthetic toxicity. However, fluoride release from the anesthetics (a cytochrome P450 process) did not appear to be required for toxicity (no protection with P450 inhibitors and no detectable inorganic fluoride release). As IF was judged to be one-third as toxic as MF, subclinical tubular injury (increased urine N-acetyl-beta-D-glucosaminidase (NAG) levels) after its use was sought in 19 surgical patients. Fifteen patients undergoing comparable operations with SF (approximately one-half as toxic as IF in vitro) and nine patients undergoing regional/ local anesthesia were controls. The IF group doubled its urinary NAG levels by the end of surgery (P < 0.005). Conversely, NAG levels remained stable in both control groups. The conclusions are that 1) currently used fluorinated anesthetics, particularly IF, share (but to a lesser degree) MFs tubulotoxic effects, 2) ATP depletion (probably due to decreased production) and Na,K-ATPase inhibition are likely contributing mechanisms, 3) fluoride is a prime determinant of this toxicity, and 4) tubular injury can be expressed at or near clinically relevant anesthetic/inorganic fluoride levels. That increased enzymuria can develop in patients after IF anesthesia suggests that the above in vitro data could have potential clinical relevance in selected patients.